2007
DOI: 10.1038/sj.onc.1210446
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of H4(D10S170) protein in ATM-dependent response to DNA damage

Abstract: H4(D10S170) gene has been identified upon its frequent rearrangement with RET in papillary thyroid tumours (RET/PTC1). The kinase ataxia telangectasia mutated (ATM) phosphorylates a limited number of downstream protein targets in response to DNA damage. We investigated the potential role of H4(D10S170) in DNA damage signaling pathways. We found that in cells treated with etoposide or ionizing radiation (IR), H4(D10S170) underwent ATM-mediated phosphorylation at Thr 434, stabilizing nuclear H4. In ataxia telang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 37 publications
(33 reference statements)
6
57
0
Order By: Relevance
“…Moreover, CCDC6 inhibits CREB1 activity by activating HDAC1 that results in a decreased acetylation status of histone H3 at the CREB1 responsive promoters. All these results, showing that CCDC6 is able to reduce CREB1 activity, account for the inhibition of cell growth induced by CCDC6, as already shown (Merolla et al, 2007).…”
Section: Ccdc6 Represses Creb1 Activitysupporting
confidence: 81%
See 3 more Smart Citations
“…Moreover, CCDC6 inhibits CREB1 activity by activating HDAC1 that results in a decreased acetylation status of histone H3 at the CREB1 responsive promoters. All these results, showing that CCDC6 is able to reduce CREB1 activity, account for the inhibition of cell growth induced by CCDC6, as already shown (Merolla et al, 2007).…”
Section: Ccdc6 Represses Creb1 Activitysupporting
confidence: 81%
“…More recently, it has been shown that CCDC6 is involved in ATM-mediated cellular response to DNA damage, supporting the idea that the impairment of CCDC6 gene function might have a function in thyroid carcinogenesis (Merolla et al, 2007). The aim of our work has been to further characterize the function of the CCDC6 protein first by searching for the interacting proteins.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…14,15 In previous work, we documented that CCDC6 (coiled-coildomain containing 6) acts as a proapoptotic protein substrate of ATM, to sustain DNA damage checkpoints in response to genotoxic events. 16,17 Moreover, CCDC6 protects genome integrity by modulating the activity of the phosphatase PP4C directed toward the dephosphorylation on S139 of the histone H2AX (gH2AX) in response to DNA damage. 18 Consistent with this, we reported that CCDC6 deficiency affects the gH2AX foci formation and the repair of the DNA DSBs.…”
mentioning
confidence: 99%